O Banco Central como uma organização de aprendizagem - Mota, Maria Gloria Marques (1999)
This study' s aim was to verify at what point the concept of learning organization can be applied to Central Bank. It argues how this concept can generate thoughts and ideas about organizational issues, as it emphasizes the development of new skills and capabilities. The essay includes the description of the model that inspired it and some complementary notions regarding the theme. The model studied was analysed and compared to the field research and the documents. Many aspects that make the Bank similar to an ideal leaming organization have been pointed out in the area of innovation in infrastructure, such as the implementation of new practices and systems. In a deeper leveI of reflection, it was verified that in relation to the practice of the fifth learning disciplines (Personal Mastery, Mental Models, Shared Vision, Team Learning and Systems Thinking), the creation of new guiding ideas, new management methods, the Central Bank does not approximate of what it is called a learning organization.